Transformasi Religiusitas Perempuan Banjar Melalui Majelis Taklim di Kalimantan Selatan - Harmina; Salamah; Fahmi Hamdi (Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the transformation of Banjar women’s religiosity through majelis taklim in South Kalimantan and to identify the forms, factors, and impacts of these religious transformations on women’s social and spiritual lives. The study employed a qualitative approach with a case study design to gain an in-depth understanding of women’s religious experiences within the Banjar cultural context. Data were collected through in-depth interviews, participatory observation, and documentation of activities conducted in several majelis taklim in South Kalimantan. Data analysis was carried out thematically through transcription, coding, categorization, and interpretation processes. The findings reveal that majelis taklim functions as a space for religious transformation that contributes to the improvement of worship practices, changes in social behavior, more polite communication patterns, the adoption of religious clothing, and the strengthening of spiritual awareness among Banjar women. These transformations are influenced by religious social environments, family support, religious leaders, majelis taklim communities, digital da’wah media, and personal spiritual needs. This study also finds that majelis taklim contributes to strengthening social solidarity, family education, women’s participation in socio-religious activities, and the formation of Islamic identity among Banjar women within the framework of local culture. The novelty of this study lies in its analysis of the relationship between majelis taklim, Banjar culture, and the reinforcement of local Muslim women’s religious identity in contemporary South Kalimantan society.